Alerting of hectometric turbulence features at Hong Kong International Airport using a short‐range LIDAR. (14th September 2020) - Hon, Kai‐Kwong; Chan, Pak‐Wai
Abstract: Small‐scale, fast‐evolving airflow disturbances, possibly due to upstream building clusters, are known to affect aircraft landing at corridor 25RA of Hong Kong International Airport (HKIA), China, under southerly or southwesterly winds. The paper presents a new algorithm, based on the concept of coherent integrated differential velocity (CIDV), for the automatic alerting of such hectometric (scale of hundreds of metres) turbulence features using short‐range LIDAR (SRL) scans at 30 m radial resolution and an observation frequency of around every 20 s by Hong Kong Observatory (HKO). The CIDV identifies the cumulative effect of coherent patches of radial velocity changes occurring along the landing flight path by comparing two consecutive sub‐minute SRL scans. Verification was conducted between June and September 2017 against a selection of relevant pilot reports, with a positive skill level observed over the whole range of the CIDV thresholds considered. When simulating a realistic setting where the SRL would issue alerts in conjunction with HKO's operational Windshear and Turbulence Warning System (WTWS), the CIDV algorithm would bring a gain in hit rate between 5% and 25%, with a corresponding increase in alert duration between 0.4% and 20%. The chosen CIDV threshold of 0.4 m·s −1 nautical mile (nm) can be physically interpreted as an average radial velocity change of 4.0 m·s −1 sustained over a distance of < 200 m (or between 2 and 3 s of flight), which agrees with reported values of crosswind changes considered significant for a landing aircraft and also pilots' perception of the characteristics of such events. Abstract : Hong Kong Observatory (HKO) employs a short‐range LIDAR (SRL) to perform hectometric, sub‐minute scans to detect turbulence possibly due to buildings at Hong Kong International Airport (HKIA). The paper presents a new alerting algorithm based on the concept of coherent integrated differential velocity (CIDV) to leverage these unique measurements with high spatio‐temporal resolution. The CIDV algorithm verifies favourably against aircraft pilot reports and adds skill to the Windshear and Turbulence Warning System (WTWS), HKO's existing operational alerting system at HKIA.